Calculation of Pressure Set-point for Coordinated Control System Based on Multi-objective Optimization. Issue 5 (March 2019) - Xiao, Li; Xu, Zhibin; Ouyang, Chunming; Zhang, Weidong
Abstract: In this paper, the calculation and optimization of pressure set-points for large scale ultra-(super-) critical unit coordinated control system are studied, which adopts a multi-objective optimization method based on particle swarm optimization to adjust the pre-machine pressure set-point for the different external load requirements.